Comparisons of microvascular and macrovascular changes in aldosteronism-related hypertension and essential hypertension - Monica Varano (Nature Portfolio, 2017)
Abstract Case-control observational study to evaluate the microvascular and macrovascular changes in patients with hypertension secondary to primary aldosteronism (PA), essential hypertension (EH) and healthy subjects. Measurements of arterial stiffness including augmentation index (AIx) and pulse wave velocity (PWV) were assessed using a TensioClinic arteriograph system. Retinal microcirculation was imaged by a Retinal Vessel Analyzer (RVA) and a non-midriatic camera (Topcon-TRC-NV2000). IMEDOS software analyzed the retinal artery diameter (RAD), retinal vein diameters (RVD) and arteriole-to-venule ratio (AVR) of the vessels coming off the optic disc. Thirty, 39 and 35 patients were included in the PA, EH and control group, respectively. The PA group showed higher PWV values compared only with the control group. The mean brachial and aortic AIx values did not show significant difference between groups. In the PA group, the mean RVD and AVR values were significantly lower than in the EH and control groups, whereas the parameters did not differ between the EH and control groups. In conclusion, AVR appears significantly modified in the PA group compared with the EH group and could represent an early and more reliable indicator of microvascular remodeling.